PARASITOLOGICAL SURVEY OF CLARIAS GARIEPINUS IN KITIRI RESERVOIR, JIGAWA STATE: PREVALENCE, INTENSITY, AND ASSOCIATED RISK FACTORS - Idris, Safiyanu; Bichi, A. H.; Umaru, Joel; Sambo, F.; Sambo, M. U.; Adam, A. A.; Abubakar, A.; Chiroma, Y. (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the prevalence, intensity, and risk factors of parasites in Clarias gariepinus from Kitiri, Dakori Malam Buba, and Rafa in Jigawa State, Nigeria, between January 2022 and December 2023. A total of 120 specimens were collected with different fishing nets and transported to the Biology Laboratory of Binyaminu Usman Polytechnic, Hadejia. Fish were morphologically identified, sexed using urogenital papilla examination, and measured for total length and weight. External examinations were conducted for ectoparasites, while the gastrointestinal tract was dissected to identify endoparasites. Results revealed sex-related differences in infestations. Male C. gariepinus had the highest infection with Rhabdochona spp. (40%), while females showed greater prevalence of Trichodina spp. (52.38%). Endoparasites were more frequent in male intestines (55%), whereas Trichodina spp. occurred predominantly on the skin (54.54%) and gills (45.45%) of females. Parasite burden was influenced by size and weight, with smaller fish (10.0–15.0 cm; 31.0–50.0 g) showing higher infestations. Spatial variation indicated the highest prevalence in Dakori Malam Buba (57.5%) and Rafa (55%), while temporal analysis showed infestations peaked in the rainy season (43.89%). These findings corroborate earlier reports of high parasite prevalence in C. gariepinus across Nigerian waters, emphasizing the role of host biology and environmental conditions in infection patterns. Continuous monitoring and effective management are therefore critical to reducing parasitic infestations in aquaculture and wild fish stocks.